Optical absorption and light scattering in microcrystalline silicon thin films and solar cells - Poruba, A.; Fejfar, A.; Remeš, Z.; Špringer, J.; Vaněček, M.; Kočka, J.; Meier, J.; Torres, P.; Shah, Arvind (My University, 2000)
Optical characterization methods were applied to a series of microcrystalline silicon thin films and solar cells deposited by the very high frequency glow discharge technique. Bulk and surface light scattering effects were analyzed. A detailed theory for evaluation of the optical absorption coefficient α from transmittance, reflectance and absorptance (with the help of constant photocurrent method) measurements in a broad spectral region is presented for the case of surface and bulk light scattering. The spectral dependence of α is interpreted in terms of defect density, disorder, crystalline/amorphous fraction and material morphology. The enhanced light absorption in microcrystalline silicon films and solar cells is mainly due to a longer optical path as the result of an efficient diffuse light scattering at the textured film surface. This light scattering effect is a key characteristic of efficient thin-film-silicon solar cells.